2012
DOI: 10.1159/000343919
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Lens Multifocality Combined with the Compensation for Corneal Spherical Aberration:A New Concept ofPresbyopia-CorrectingIntraocular Lens

Abstract: The outcomes of a prospective consecutive study aimed at evaluating the visual and refractive benefit after cataract surgery with the implantation of the aspheric diffractive multifocal intraocular lens (IOL) Tecnis ZMB00 (Abbott Medical Optics) are reported. A total of 31 eyes of 19 patients (age range, 40 to 81 years) underwent phacoemulsification surgery with implantation of this aspheric multifocal IOL. At 6 months after surgery, postoperative spherical equivalent was within ±1.00 D in 96.8% of eyes, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
16
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 15 publications
(26 reference statements)
8
16
0
3
Order By: Relevance
“…In agreement with this, the level of predictability of the achieved refractive correction was good, with 98.4% of eyes with a postoperative SE within ±1.0 D of emmetropia. These visual and refractive outcomes are consistent with those reported by previous authors for the ZMB00 IOL3–5 7 12 13 and for other modalities of diffractive multifocal IOLs 2 5 6 14–18…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with this, the level of predictability of the achieved refractive correction was good, with 98.4% of eyes with a postoperative SE within ±1.0 D of emmetropia. These visual and refractive outcomes are consistent with those reported by previous authors for the ZMB00 IOL3–5 7 12 13 and for other modalities of diffractive multifocal IOLs 2 5 6 14–18…”
Section: Discussionsupporting
confidence: 92%
“…All of them agree on reporting good functional distance and near visual outcomes and therefore confirm the ability of this IOL platform and diffractive pattern to restore the visual function at such distances after cataract surgery 3–5 7 12 13. Lubin´ski et al 12 have recently reported mean values of logMAR UDVA and UNVA of −0.10±0.13 and −0.02±0.12, respectively, at 6 months after cataract surgery with implantation of the Tecnis ZMB00 IOL.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Diffraktive MIOL werden außerdem in der eingearbeiteten Struktur der Lichtverteilung unterschieden. Entweder wird das einfallende Licht auf der gesamten Optikfläche segmental aufgeteilt [9,15], wobei ein Teil der IOL das Licht für die Ferne und der andere für die Nähe bündelt, oder das Licht wird durch die Kombination einer zentralen diffraktiven Optik mit umgebender monofokaler Optik (für den Fernpunkt) verteilt [16]. Durch den zusätzlichen Einsatz der Apodisation lässt sich bei diffraktiven Designs das einfallende Licht zusätzlich in unterschiedlichen Intensitäten auf die einzelnen Brennpunkte verteilen [17].…”
Section: Discussionunclassified